Efficacy, durability, and safety of intravitreal faricimab with extended dosing up to every 16 weeks in patients with diabetic macular oedema (YOSEMITE and RHINE): two randomised, double-masked, phase 3 trials. Issue 10326 (19th February 2022) - Wykoff, Charles C; Abreu, Francis; Adamis, Anthony P; Basu, Karen; Eichenbaum, David A; Haskova, Zdenka; Lin, Hugh; Loewenstein, Anat; Mohan, Shaun; Pearce, Ian A; Sakamoto, Taiji; Schlottmann, Patricio G; et al.
Summary: Background: To reduce treatment burden and optimise patient outcomes in diabetic macular oedema, we present 1-year results from two phase 3 trials of faricimab, a novel angiopoietin-2 and vascular endothelial growth factor-A bispecific antibody. Methods: YOSEMITE and RHINE were randomised, double-masked, non-inferiority trials across 353 sites worldwide. Adults with vision loss due to centre-involving diabetic macular oedema were randomly assigned (1:1:1) to intravitreal faricimab 6·0 mg every 8 weeks, faricimab 6·0 mg per personalised treatment interval (PTI), or aflibercept 2·0 mg every 8 weeks up to week 100. PTI dosing intervals were extended, maintained, or reduced (every 4 weeks up to every 16 weeks) based on disease activity at active dosing visits. The primary endpoint was mean change in best-corrected visual acuity at 1 year, averaged over weeks 48, 52, and 56. Efficacy analyses included the intention-to-treat population (non-inferiority margin 4 Early Treatment Diabetic Retinopathy Study [ETDRS] letters); safety analyses included patients with at least one dose of study treatment. These trials are registered with ClinicalTrials.gov (YOSEMITE NCT03622580 and RHINE NCT03622593 ). Findings: 3247 patients were screened for eligibility in YOSEMITE (n=1532) and RHINE (n=1715). After exclusions, 940 patients were enrolled into YOSEMITE between Sept 5, 2018, and Sept 19, 2019, and 951 patients were enrolled into RHINE between Oct 9, 2018, and Sept 20, 2019. These 1891 patients were randomly assigned to faricimab every 8 weeks (YOSEMITE n=315, RHINE n=317), faricimab PTI (n=313, n=319), or aflibercept every 8 weeks (n=312, n=315). Non-inferiority for the primary endpoint was achieved with faricimab every 8 weeks (adjusted mean vs aflibercept every 8 weeks in YOSEMITE 10·7 ETDRS letters [97·52% CI 9·4 to 12·0] vs 10·9 ETDRS letters [9·6 to 12·2], difference −0·2 ETDRS letters [−2·0 to 1·6]; RHINE 11·8 ETDRS letters [10·6 to 13·0] vs 10·3 ETDRS letters [9·1 to 11·4] letters, difference 1·5 ETDRS letters [−0·1 to 3·2]) and faricimab PTI (YOSEMITE 11·6 ETDRS letters [10·3 to 12·9], difference 0·7 ETDRS letters [−1·1 to 2·5]; RHINE 10·8 ETDRS letters [9·6 to 11·9], difference 0·5 ETDRS letters [−1·1 to 2·1]). Incidence of ocular adverse events was comparable between faricimab every 8 weeks (YOSEMITE n=98 [31%], RHINE n=137 [43%]), faricimab PTI (n=106 [34%], n=119 [37%]), and aflibercept every 8 weeks (n=102 [33%], n=113 [36%]). Interpretation: Robust vision gains and anatomical improvements with faricimab were achieved with adjustable dosing up to every 16 weeks, demonstrating the potential for faricimab to extend the durability of treatment for patients with diabetic macular oedema. Funding: F Hoffmann-La Roche.